Acute inflammatory response following lower-and upper-body wingate anaerobic test in elite gymnasts in relation to iron status - Waldzinski, T.; Kochanowicz, A.; Niespodzinski, B.; Brzezinska, P.; Kochanowicz, M.; Antosiewicz, J.; Mieszkowski, J. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Artistic gymnastics is one of the most demanding sport disciplines, with the athletes demonstrating extremely high levels of explosive power and strength. Currently, knowledge of the effect of gymnastic training adaptation on exercise-induced inflammatory response is limited. The aim of the study was to evaluate inflammatory response following lower- and upper-body high-intensity exercise in relation to the iron status in gymnasts and non-athletes. METHODS: Sixteen elite male artistic gymnasts (EAG, 20.6 ± 3.3 years old) and 16 physically active men (PAM, 19.9 ± 1.0 years old) participated in the study. Venous blood samples were taken before, and 5 min and 60 min after two variants of Wingate anaerobic test (WAnT), upper-body and lower-body WAnT. Basal iron metabolism (serum iron and ferritin) and acute responses of selected inflammatory response markers [interleukin (IL) 6, IL-10, and tumor necrosis factor *] were analyzed. RESULTS: EAG performed significantly better during upper-body WAnT than PAM in terms of the relative mean power and peak power. The increase in IL-6 levels after upper-body WAnT was higher in EAG than that in PAM; the opposite was observed after lower-body WAnT. IL-10 levels were higher in EAG than those in PAM and tumor necrosis factor * levels were higher in PAM than those in EAG only after lower-body WAnT. The changes in IL-10 correlated with baseline serum iron and ferritin in PAM. CONCLUSION: gymnastic training is associated with the attenuation of iron dependent post-exercise anti-inflammatory cytokine secretion.